2020
DOI: 10.1146/annurev-virology-020420-014025
|View full text |Cite
|
Sign up to set email alerts
|

Herpesvirus Epigenetic Reprogramming and Oncogenesis

Abstract: Among all of the known biological carcinogens, Epstein-Barr virus (EBV) and Kaposi's sarcoma-associated herpesvirus (KSHV) are two of the classical oncogenic herpesviruses known to induce the oncogenic phenotype. Many studies have revealed important functions related to epigenetic alterations of the EBV and KSHV genomes that mediate oncogenesis, but the detailed mechanisms are not fully understood. It is also challenging to fully describe the critical cellular events that drive oncogenesis as well as a compreh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
25
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(27 citation statements)
references
References 149 publications
0
25
0
Order By: Relevance
“…EBV-associated cancers such as gastric cancer, nasopharyngeal carcinoma and Burkitt’s lymphoma are characterized by extensive hypermethylation of the host DNA compared with non-infected tumors and cell culture studies have illustrated that EBV infection induces de novo methylation [ 45 , 111 , 118 , 119 , 120 , 121 , 122 ]. Many of the genes whose expression is affected by EBV-induced methylation code for proteins involved in cell cycle control, signaling pathways, apoptosis, invasion and migration [ 45 , 111 , 122 , 123 ]. Some of these genes will be discussed, as well as the viral proteins involved in their methylation.…”
Section: Oncoviruses and Host Cell Dna Methylationmentioning
confidence: 99%
See 3 more Smart Citations
“…EBV-associated cancers such as gastric cancer, nasopharyngeal carcinoma and Burkitt’s lymphoma are characterized by extensive hypermethylation of the host DNA compared with non-infected tumors and cell culture studies have illustrated that EBV infection induces de novo methylation [ 45 , 111 , 118 , 119 , 120 , 121 , 122 ]. Many of the genes whose expression is affected by EBV-induced methylation code for proteins involved in cell cycle control, signaling pathways, apoptosis, invasion and migration [ 45 , 111 , 122 , 123 ]. Some of these genes will be discussed, as well as the viral proteins involved in their methylation.…”
Section: Oncoviruses and Host Cell Dna Methylationmentioning
confidence: 99%
“…Some of the genes that were hypermethylated in KSHV-infected PEL cell lines included CDNK2A , CDH1 and CDH13 (cadherin 1 and 13), LDHB (lactate dehydrogenase B), HLTF (helicase like transcription factor, a member of the chromatin remodeling SWI/SNF family), CCND2 (cyclin D2). The authors showed that KHSV LANA recruited DNMT3A to chromatin, and induced hypermethylation and transcriptional inactivation of these genes [ 43 , 44 , 45 ]. LANA may not only repress transcription of cellular genes by inducing hypermethylation, but it may potentiate transcriptional inhibition through recruiting the transcriptional repressor methyl CpG binding protein 2 (MeCP2), which interacts with LANA [ 46 ].…”
Section: Oncoviruses and Host Cell Dna Methylationmentioning
confidence: 99%
See 2 more Smart Citations
“…For most individuals, lifelong EBV colonization of the memory B-cell compartment is asymptomatic. Nonetheless, EBV is associated with 200,000 human cancers per year, including Burkitt lymphoma, post-transplant lymphoproliferative diseases, Hodgkin lymphoma, gastric and nasopharyngeal carcinoma (1,2). Endemic Burkitt lymphoma caused by EBV remains the most common childhood cancer in sub-Saharan Africa (3)(4)(5).…”
Section: Introductionmentioning
confidence: 99%